HYBRID ERA ON BIG DATA ANALYTICS PLATFORMS - Raju, S; Krishna, E; Harika, G; Krishna, E (The journal of contemporary issues in business and government, 2020)
The key purpose of this paper is to provide an unbiased assessment of different systems appropriate for vast processing of facts. Numerous technological systems available for broad knowledge analytics are analysed in this paper and comprehensive reviews are addressed on their strengths and limitations. Similarly, a broad collection of guidelines for adapting knowledge mining for massive statistical research was addressed wart its suitability to cope with actual-global computing problems. Through the successful introduction of these well developed and commonly utilized knowledge mining algorithms, the destiny patterns of big information processing and analysis can be anticipated to focus on the strengths of the technological frameworks and platforms available. Hybrid strategies (integration of or broader structures) can be best adapted for a chosen knowledge mining algorithm which can be well adaptable and can be processed in real time. Keywords huge facts; mass data analytics; cloud computing; mining statistics; computer research; systems of large facts;